2015
DOI: 10.1091/mbc.e14-09-1398
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule-dependent transport and dynamics of vimentin intermediate filaments

Abstract: Vimentin intermediate filaments-structures that were considered extremely stable-are in fact very dynamic. Filaments are actively transported throughout the cell along microtubules. In addition, filaments undergo constant rearrangement by robust severing and reannealing but never completely disassemble and reassemble.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
125
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(136 citation statements)
references
References 43 publications
11
125
0
Order By: Relevance
“…In agreement with our previously published results, we observed the presence of some short and uniformly red segments of filaments that have been transported along microtubules outside the photoconverted zone ( Fig. 4A) (16). However, no dual-color filaments were observed outside the photoconverted area in these cells, even 15 min after photoconversion (Fig.…”
Section: Y117l Vimentin Does Not Exchange In the Context Of Mature VIsupporting
confidence: 93%
See 2 more Smart Citations
“…In agreement with our previously published results, we observed the presence of some short and uniformly red segments of filaments that have been transported along microtubules outside the photoconverted zone ( Fig. 4A) (16). However, no dual-color filaments were observed outside the photoconverted area in these cells, even 15 min after photoconversion (Fig.…”
Section: Y117l Vimentin Does Not Exchange In the Context Of Mature VIsupporting
confidence: 93%
“…Previous studies have shown that VIFs are very stable because the exchange of fragments or smaller subunits along the length of mature filaments is very slow (16,22). The present study revealed a very fast process of subunit exchange among ULFs assembled from vimentin Y117L .…”
Section: Y117l Vimentin Does Not Exchange In the Context Of Mature VIsupporting
confidence: 58%
See 1 more Smart Citation
“…In our case, we studied: the relationship between the sizes and lifetimes of clathrin-coated pits (CCPs), the role of actin in clathrin-mediated endocytosis, the dynamics at clathrin patches and hot spots of CCP formation, the formation of nanoscale actin rings, the diversity of caveolin-rich structures, and the nanoscale recruitment of a-actinin during the formation of actin-rich structures. Elsewhere, in the past year or two live-cell SIM has been used to investigate the dynamics of MreB filaments in bacteria (9) and cortical microtubules (10), microtubule-dependent transport of vimentin filaments (11), vesicle formation at the inner nuclear membrane (12), centrosome assembly in Drosophila (13), a dorsal actomyosin network that drives cell motility (14), and the assembly of isoforms of nonmuscle myosin II (15) and combinations of myosin II and myosin 18 (16) into bipolar filaments. We look forward to revisiting our debate with Sahl et al a decade from now to see which SR methods have had the broadest effect in biology.…”
mentioning
confidence: 99%
“…The presence of vimentin and crystalline alpha proteins increases stability of the cytoskeleton by reducing depolymerization. 56,57 The results of decreased depolymerization is an increase of the cytoskeleton with membrane protrusion, tumor progression and metastasis, as well as a change of polarization during mitosis leading to cellular pleomorphism. 58,59 The presence of HSP 60 in the primary tumor indicates the refurbishment of misfolding proteins and affects the stability of the cytoskeleton, thus enhancing the progression of carcinogenesis.…”
Section: Resultsmentioning
confidence: 99%